Analysis of the Effects of Sharia Governance and Corporate Social Responsibility on Corporate Reputation and Financial Performance in Indonesian Sharia Multinational Companies - Judijanto, Loso; Ansori, Tirangga; Rusdi, Rusdi (Westscience Press, 2024)
This study investigates the interplay between Sharia Governance, Corporate Social Responsibility (CSR), Corporate Reputation, and Financial Performance in Indonesian Sharia multinational companies. A quantitative approach using Structural Equation Modeling with Partial Least Squares (PLS) analysis is employed to analyze data collected from 200 employees within selected companies. The results indicate significant positive relationships between Sharia Governance and both Corporate Reputation and Financial Performance, as well as between CSR and these outcomes. Furthermore, Corporate Reputation partially mediates the effects of Sharia Governance and CSR on Financial Performance. The findings underscore the importance of ethical governance and socially responsible practices in enhancing organizational outcomes, offering practical insights for managers and policymakers in Indonesian Sharia multinational companies.